Facile synthesis of amorphous Co engineered FePO4: As an efficient electrocatalyst for hydrogen and oxygen evolution reactions - Khan, Safyan Akram (International journal of hydrogen energy, 2025)
Water-based hydrogen production has established itself as a competitive and feasible substitute for fossil fuels. Thus, the creation of effective electrocatalysts for the enduring generation of hydrogen has been the subject of extensive research. In this work, we synthesize Co engineered FePO4 (Co–FePO4) using a sophisticated hydrothermal synthesis technique. The fabricated materials are then employed for various analytical techniques. Then tested for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) using several electrochemical tests like electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), and cyclic voltammetry (CV). The Co–FePO4/GC attained overpotentials of 320 mV (OER) and 174 mV (HER). Its improved catalytic efficiency is further demonstrated by its reduced Tafel slopes for OER (64 mV dec−1) and HER (93 mV dec−1) for HER, which is compared to the state-of-the-art catalysts. The stability of the synthesized Co–FePO4 is further confirmed by chronoamperometry, and remains stable up to 40 h for HER, and 32 h for OER. Hence, Co–FePO4 is a promising contender for cutting-edge electrochemical energy applications because of these unique and remarkable properties. [Display omitted] •The Co engineered FePO4 are prepared via hydrothermal reaction.•A porous, amorphous Co–FePO4 nanoparticles are active for both HER and OER.•Co engineered FePO4 attained an overpotentials of 320 mV for OER.•It also shows Tafel slopes of 64 mV dec−1 for OER, and 94 mV dec−1 for HER.•The fabricated material shows good stability of 40 h for HER.